A history of the book in America. - Nord, David Paul; Rubin, Joan Shelley, 1947-; Schudson, Michael (History of the book in America, 2009)
V. 1. The colonial book in the Atlantic world: This book carries the interrelated stories of publishing, writing, and reading from the beginning of the colonial period in America up to 1790. v. 2 An Extensive Republic: This volume documents the development of a distinctive culture of print in the new American republic. v. 3. The industrial book 1840-1880: This volume covers the creation, distribution, and uses of print and books in the mid-nineteenth century, when a truly national book trade emerged. v. 4. Print in Motion: In a period characterized by expanding markets, national consolidation, and social upheaval, print culture picked up momentum as the nineteenth century turned into the twentieth. v. 5. The Enduring Book: This volume addresses the economic, social, and cultural shifts affecting print culture from Word War II to the present.